Ritual, emotion, and materiality in the early Christian world - Al-Suadi, Soham; Ascough, Richard S.; DeMaris, Richard E. ca. 20./21. Jh. (Ritual in the ancient Mediterranean, 2022)
"This volume advances our understanding of early Christianity as a lived religion by approaching it through its rites, the emotions and affects surrounding those rites, and the material setting for the practice of them. The connections between emotions and ritual, between rites and their materiality, and between emotions and their physical manifestation in ancient Mediterranean culture have been inadequately explored as yet, especially with regard to early Christianity and its water and dining rites. Readers will find all three areas-ritual, emotion, and materiality-engaged in this exemplary interdisciplinary study, which provides fresh insights into early Christianity and its world. Ritual, Emotion, and Materiality in the Early Christian World will be of special interest to interdisciplinary-minded researchers, seminarians, and students who are attentive to theory and method, and those with an interest in the New Testament and earliest Christianity. It will also appeal to those working on ancient Jewish and Greco-Roman religion, emotion, and ritual from a comparative standpoint"--